GIS BASED ENTROPY- ELECTRE II FOR PLANNING SITING MAPPING HYDROGRAPHY-OCEANOGRAPHY IN REGION ALKI I - Ahmadi Ahmadi; Heri Ebtanta; Budisantoso Wirjodirdjo (Indonesian Naval Technology College - Sekolah Tinggi Teknologi Angkatan Laut - STTAL, 2016)
Navigational chart is a dynamic map that should always be updated to ensure safety in navigation at sea. Indonesia's vast territorial waters is a challenge for policy makers to be able to prioritize areas that must be mapped / updated. ELECTRE II method is widely recognized can be used to analyze a policy that involves both qualitative and quantitative criteria. This method involves the manufacture preceded by a directed graph that represents outranking relationship with Threshold determine concordance and discordance. Entropy methods are used to provide the weighting of criteria. This method was chosen because it can accommodate with some decision-makers or experts. The incorporation of multi-criteria method with GIS is very useful for solving problems related to geospatial. Sensitivity analysis is done by changing some threshold value. This research was conducted in waters ALKI I.